Valuasi Ekonomi Konversi Lahan Pertanian Di Kawasan Aerotropolis Kulon Progo - Awani Dilha Merdekawati (Jurnal Plano Buana, 2021)
The construction of the Yogyakarta International Airport (YIA) in Temon District, Kulon Progo Regency has various impacts, one of which is the growth of the aerotropolis area which causes changes in land use. The conversion of land use, causing any difference in economic valuation. The purpose of this research is to determine the impact of agricultural land conversion through economic value of the Kulon Progo aerotropolis area, with case studies in Palihan, Sindutan, Jangkaran, Kebonrejo and Glagah village. This research uses a non-empirical study method while research approach uses a mixed quantitative and qualitative approach. The analysis used in the form of land use change by digitizing the image (CSTR) of land and geo-referencing overlay in ArcGis, as well as economic valuation analysis. The result shows that changes in economic value have decreased for the use of agricultural and pond fields, while for settlements, the economic value after the construction of YIA has increased.